OPTIMALISASI PRODUKSI DENGAN MENGANALISIS PEKERJAAN MENGGUNAKAN METODE MOST (Studi Kasus PT. X di Palembang) - Zahri, Amiluddin; Makmuri, Muhammad Kumroni (Jurnal Tekno, 2019)
A job is completed efficiently would say when lasted the shortest completion time. Measuring success of a production system in the industry are usually expressed in terms of productivity or the size of the input and output generated. Measurement standard at this time are made directly by the method stopwatch and indirectly with MOST methods (Maynard Operation Sequence Technique). Results of measurements using a standard time stop watch is 179,62 Second, with MOST measurements before the analysis is 123,73, most after the analisis is 75,25 second. Raw output using the old work is 200 Unit newspaper first hour , and use the most is the raw output of 478 Unit newspaper first hour. Seeing the results of the study suggested that the company may consider to perform the application of research results have been obtained